Interactive e-module design integrating deep learning and Tri-N to Improve elementary students’ learning independence - Akbar Al Masjid; Tiza Ariesta Saputri; Banun Havifah Cahyo Khosiyono; Jamiu Temitope Sulaimon (Bulletin of Educational Management and Innovation, 2026)
Background: The level of learning independence among elementary school students is still relatively inadequate. One contributing factor is the insufficient utilization of interactive digital learning media in classroom instruction. Learning activities are predominantly carried out using traditional approaches, which tend to limit students’ opportunities to actively construct knowledge and learn autonomously. Therefore, there is a clear need to introduce innovative digital learning tools that can effectively promote students’ independent learning abilities. Purpose: This study seeks to design and produce an interactive e-module for Indonesian language learning that applies a deep learning approach integrated with the Tri-N philosophy, with the aim of enhancing students’ learning independence. Method: This study employed a Research and Development (R&D) methodology utilizing the ADDIE framework, which includes the stages of analysis, design, development, implementation, and evaluation. The data collection techniques for this research use interview, questionnaire and observation techniques. The participants of this study were elementary school students involved in both limited-scale and wider-scale implementation trials. The data analysis technique uses qualitative and quantitative descriptive with N-Gain Score and T-test. Findings: The results revealed that the developed e-module met the criteria of validity, practicality, and effectiveness. Expert validation yielded an average score of 91.5% (very feasible), while teacher and student responses reached 93.2% and 92.4% respectively, indicating excellent practicality. Furthermore, students’ learning independence increased by 21.6%, supported by higher engagement and motivation during the learning process. The integration of deep learning dimensions—mindful, meaningful, and joyful learning—combined with Tri-N stages effectively enhanced students’ reflective thinking and creative expression in understanding figurative language. The research concludes that this e-module serves as an innovative and culturally grounded digital learning resource aligned with the Merdeka Belajar curriculum, supporting the development of autonomous and creative learners in Indonesian elementary education.